Novel frameshift CTSF mutation causing kufs disease type B mimicking frontotemporal dementia-parkinsonism. Issue 1 (2nd January 2022) - Gultekin, Murat; Tufekcioglu, Zeynep; Baydemir, Recep
ABSTRACT: Adult-onset neuronal ceroid lipofuscinoses (ANCLs, Kufs disease-KD) are rare, inherited, progressive, neurodegenerative, lysosomal storage diseases. Mutations in cathepsin F (CTSF) were linked to KD type B. Conversely, Frontotemporal dementia (FTD) is the second most common type of presenile dementia and Parkinsonism is a mostly common accompanying feature. Due to pronounced behavioral, cognitive, and motor features in the patients with KD type B, mutations in CTSF may resemble FTD-parkinsonism. Here, we present a case of KD type B with a novel homozygous frameshift pathogenic variant (p.Gly439Alafs*36) in the Cathepsin F (CTSF) gene presenting behavioral changes, cognitive disturbances and parkinsonism with a family history mimicking FTD-parkinsonism.